COMPARATIVE LITERATURE IN FAULKNER’S A ROSE FOR EMILY AND PRAMOEDYA’S PANGGIL SAJA AKU KARTINI - masofa, ima (Faculty of Letters, Dr. Soetomo University, 2018)
Abstract: This article analyzes comparative literature in Faulkner’s A Rose For Emily and Pramoedya’s Panggil Aku Kartini Saja.The researcher analyzes comparative literature that uses American School to compare how the society’s role effects to the main characters in Faulkner’s A Rose For Emily and Pramoedya’s Panggil Aku Kartini Saja.. Faulkner’s A Rose for Emily and Pramoedya’s Panggil Aku Kartini Saja have same backgrounds of women’s life. Kartini in Pramoedya’s Panggil Aku Kartini Saja and Emily in Faulkner’s A Rose for Emily are from noble that rule Kartini and Emily. This article attempts to find similarities and dissimilarities of the woman in Faulkner’s A Rose For Emily and Pramoedya’s Panggil Aku Kartini Saja.The results of this research can be formulated as follows: 1)Similarities are that both Emily and Kartini are from noble family. 2) Differences are that Kartini can influence women at the time to get their right,but Emily lives in fear because of her society rule.Keywords: Comparative Literature,American School,